Antioxidant potential of some Sudanese medicinal plants used in traditional medicine - EL-Kamali, Hatil; E. M. Hamed, Sana (International Journal of Scientific World, 2015)
In the present work methanolic and water extracts of 19 medicinal plants, commonly used in Sudanese folk medicines against gastrointestinal tract, infectious diseases were investigated for their antioxidant activity. Antioxidant assays were carried out by using different in vitro models such as DPPH (2, 2-diphenyl-1picrylhydrazyl) radical scavenging and Iron chelating activity. Methanolic and water extracts of Punica granatum showed the highest total antioxidant activity of 71±0.03 and 73±0.01 respectively. The antioxidant activities of water extracts were poor when compared to the methanol extract. The iron chelating power of methanol and aqueous extracts of Commiphora myrrha 58±0.01 and Azadirachta indica 57±0.20 respectively.